Number of excisions required to obtain clear surgical margins and prognostic value of AJCC T category for patients with eyelid melanoma. Issue 12 (22nd July 2014) - Yin, Vivian T; Warneke, Carla L; Merritt, Helen A; Esmaeli, Bita
Abstract : Aims: To determine the number of excisions needed to achieve clear margins and the prognostic value of the 7th edition of American Joint Committee on Cancer (AJCC) classification for eyelid melanoma. Methods: Retrospective chart review of consecutive patients treated for eyelid melanoma from January 2006 through May 2013 by the senior author at a tertiary care cancer centre. Results: Of the 64 patients (25 men and 39 women), clear surgical margins were achieved with a single excision in 38 patients (62%), 2 excisions in 21 patients (34%), and 3 excisions in 2 patients (3%). Need for repeat excision was not correlated with the size of the surgical margin (p=0.14) or AJCC TNM classification (p=0.15). Nodal disease at presentation was significantly associated with T category greater than T2b (p=0.0026) and shorter time to disease progression (p=0.007). Patients followed for a minimum of 1 year with T category greater than T2b had a significantly higher risk of nodal or distant metastasis (p=0.0061). Conclusions: More than a third of patients with eyelid melanoma required more than 1 excision to achieve clear margins, supporting delayed reconstruction for eyelid melanoma. Nodal metastasis at presentation was significantly correlated with AJCC T category and time to progression.